Conditions for exponential stability and dichotomy of pulse linear extensions of dynamical systems on a torus - Ali, N. A.; Yanchuk, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
Conditions for exponential stability and dichotomy of pulse linear extensions of dynamical systems on a torus are investigated.